Structural biology approach to biotechnological problems - Iermak, Iuliia (Jihočeská univerzita, 2017)
Enhancement of the catalytic performance of various enzymes in the reaction systems requires advanced studies of enzymes' structure-function relationships. The obtained information is used to engineer favourable enzyme variants exhibiting beneficial properties for applications in biotechnology. In the thesis X-ray crystallographic analysis was successfully employed for the structure-functional characterization of the glyceraldehyde dehydrogenase from thermophilic bacterium Thermoplasma acidophilum (TaAlDH). This enzyme is one of the key enzymes in the cell-free system for the production of ethanol or isobutanol from glucose. The second part of the thesis describes optimization by structure-guided engineering of the haloalkane dehalogenase LinB from the soil bacterium Sphingobium japonicum UT26, used for the effective degradation of halogenated environmental pollutants.
Structural biology approach to biotechnological problems